2021
DOI: 10.1097/ccm.0000000000005300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Multicomponent Sepsis Transition and Recovery Program on Mortality and Readmissions After Sepsis: The Improving Morbidity During Post-Acute Care Transitions for Sepsis Randomized Clinical Trial*

Abstract: PATIENTS:Eligible patients hospitalized for suspected sepsis and deemed highrisk for mortality or readmission by validated internal risk models. INTERVENTIONS:Patients were randomized to receive usual care alone (i.e., routine transition support, outpatient care; n = 342) or additional Sepsis Transition And Recovery support (n = 349). The 30-day intervention involved a multicomponent transition service led by a nurse navigator through telephone and electronic health record communication to facilitate best prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…To understand the incremental predictive value of discharge CBCD parameters, we fit multivariable logistic regression models and used the area under the receiver operating characteristics (AUROC) and likelihood ratio tests to determine significant improvement over a base model using clinical variables alone. Clinical variables selected for inclusion in the base model were all previously associated with risk of post-hospitalization death or rehospitalization in other publications (7)(8)(9)37). Additionally, we fit a full model using clinical variables and all eight CBCD parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the incremental predictive value of discharge CBCD parameters, we fit multivariable logistic regression models and used the area under the receiver operating characteristics (AUROC) and likelihood ratio tests to determine significant improvement over a base model using clinical variables alone. Clinical variables selected for inclusion in the base model were all previously associated with risk of post-hospitalization death or rehospitalization in other publications (7)(8)(9)37). Additionally, we fit a full model using clinical variables and all eight CBCD parameters.…”
Section: Discussionmentioning
confidence: 99%
“…While there has been increased attention to longerterm morbidity and mortality after sepsis, targeted therapies to prevent these sequelae are lacking (4)(5)(6). In addition, predicting post-acute sequelae, particularly rehospitalization, remains challenging with predictive models performing only modestly (7)(8)(9)(10). Heterogeneity in sepsis and sepsis survivorship is a major factor complicating the development of predictive models and application of therapies directed at improving long-term outcomes (4,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2021 adult Surviving Sepsis Campaign guidelines recommend routine follow-up and assessment for new sepsis-related sequelae after hospital discharge, but no similar recommendation exists for children . Structured postsepsis follow-up programs incorporating telephone follow-up, patient and family education, care coordination, screening, and communication with outpatient health care professionals have been feasible in high-resource settings, but more work is needed to make such programs broadly accessible. Second, our study suggests that dedicated research is needed to better understand and mitigate the development and progression of comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This model of support may miss an early window of vulnerability among ARF survivors, as suggested by a pilot randomized trial [47]. The pragmatic IMPACTS trial also suggested that a nurse navigator might improve outcomes among sepsis survivors [59]. The IMPACTS intervention included symptom monitoring, medication review, and targeted palliative care referrals.…”
Section: Discussionmentioning
confidence: 99%